2019
DOI: 10.1101/2019.12.30.891085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kirrel3-mediated synapse formation is attenuated by disease-associated missense variants

Abstract: word count: 209 21

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…In support of additional dimerization sites, Gerke et al (2003) reported evidence that dimerization was not limited to any single domain within Kirrel1 and the related Nephrin. Furthermore, a large number of human mutations affecting Kirrel3 function in the ectodomain, but outside D1, have been identified (summarized in Taylor et al, 2020). To test whether Kirrel ectodomains can form dimers using interfaces we did not identify in our crystal structures, we used analytical ultracentrifugation to quantify dimerization of Kirrel2 and Kirrel3 ectodomains and one D1 interface mutant, Kirrel3 Q128A.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In support of additional dimerization sites, Gerke et al (2003) reported evidence that dimerization was not limited to any single domain within Kirrel1 and the related Nephrin. Furthermore, a large number of human mutations affecting Kirrel3 function in the ectodomain, but outside D1, have been identified (summarized in Taylor et al, 2020). To test whether Kirrel ectodomains can form dimers using interfaces we did not identify in our crystal structures, we used analytical ultracentrifugation to quantify dimerization of Kirrel2 and Kirrel3 ectodomains and one D1 interface mutant, Kirrel3 Q128A.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore studied the entire Kirrel2 and Kirrel3 ectodomains using Multiple lines of evidence support the idea that Kirrels and its homologs act as more than "molecular Velcro" in nervous system development. In the hippocampus, Kirrel3 homophilic adhesion is required, but not sufficient for synapse formation, and mutations that occur outside of the D1 binding domains and even in the intracellular domains prevent synapse formation, despite being able to form homodimeric complexes (Taylor et al, 2020). The C. elegans homologs SYG-1 and SYG-2 were shown to be signaling receptors, whose functions depend on the exact geometry of ectodomain dimerization also mediated by D1 (Özkan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations